STRATEGI MANAJEMEN TENAGA PENDIDIK UNTUK PENINGKATAN KUALITAS PENDIDIKAN DI SMKN 2 SAWAHLUNTO - Febrina, Rifka; Hutabarat, Rinto; Yani, Nurmaningsih; Yuliani, Tri (STKIP Pesisir Selatan, 2025)
The management of educator is a crucial determinant in the improvement of education quality. In the context of SMKN 2 Sawahlunto, the main challenge is related to the lack of educators and the development of essential competencies needed. This investigation seeks to examine the strategies used in managing the educator workforce with the aim of improving the quality of education. The main emphasis is on assessing the quantity and competence of educators, in addition to forecasting future educational personnel needs. This research uses a descriptive qualitative methodology, utilizing data collection techniques that include document analysis, interviews with administrative personnel and educators, as well as direct observation of educator management practices. Narrative analysis was conducted to explain the prevailing strategies. The findings indicate that careful planning, which includes a thorough assessment of educator requirements and professional development initiatives, is crucial. Educational institutions are encouraged to implement transparent selection processes and to facilitate continuous training opportunities. In addition, the establishment of a well-defined organizational structure and strict monitoring of educator performance play a crucial role in the successful implementation of effective strategies. A comprehensive approach to educator personnel management is expected to significantly improve the quality of education at SMKN 2 Sawahlunto.